Reversible Covalent PROTACs: Novel and Efficient Targeted Degradation Strategy - Yuan, Minghua; Chu, Yanan; Duan, Yongtao (Frontiers in Chemistry, 2021)
The proteolysis targeting chimeras (PROTACs), which are composed of a target protein binding moiety, a linker, and an E3 ubiquitin ligase binder, have been a promising strategy for drug design and discovery. Given the advantages of potency, selectivity, and drug resistance over inhibitors, several PROTACs have been reported in literature, which mostly focus on noncovalent or irreversible covalent binding to the target proteins. However, it must be noted that noncovalent or irreversible PROTACs have several drawbacks such as weak binding affinity and unpredictable off-target effects. Reversible covalent PROTACs, with properties of enhanced potency, selectivity, and long duration of action, have attracted an increasing amount of attention. Here, we propose a comparison between these three patterns and highlight that reversible covalent PROTACs could pave the way for a wide variety of challenging target degradations.